2021
DOI: 10.14309/ajg.0000000000001503
|View full text |Cite|
|
Sign up to set email alerts
|

A 2-Step Strategy Combining FIB-4 With Transient Elastography and Ultrasound Predicted Liver Cancer After HCV Cure

Abstract: INTRODUCTION: Despite the direct-acting antiviral therapy has dramatically decreased the likelihood of having liver-related complications and extrahepatic outcomes, the risk of developing hepatocellular carcinoma (HCC) is not totally eliminated after sustained virological response (SVR). We aimed to develop an easy-to-apply strategy to be adopted in clinical practice for accurately classifying the HCC risk in hepatitis C virus patients after SVR. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…A recent multicenter prospective study, including more than 1000 patients who achieved SVR after treatment with DAAs, has reported that patients with VCTE values >10 kPa or with cirrhosis assessed by US before the treatment had a higher risk for HCC if the FIB-4 was >3.25 with respect to patients with FIB-4 < 3.25. 54 The rate of HCC occurrence was 8.8% in the former group and 2.4% in the latter group. Of note, patients who maintained FIB-4 >3.25 and VCTE values >10 kPa after SVR had the highest risk of HCC occurrence (13.7%).…”
Section: Prediction Of Clinical Outcomesmentioning
confidence: 86%
“…A recent multicenter prospective study, including more than 1000 patients who achieved SVR after treatment with DAAs, has reported that patients with VCTE values >10 kPa or with cirrhosis assessed by US before the treatment had a higher risk for HCC if the FIB-4 was >3.25 with respect to patients with FIB-4 < 3.25. 54 The rate of HCC occurrence was 8.8% in the former group and 2.4% in the latter group. Of note, patients who maintained FIB-4 >3.25 and VCTE values >10 kPa after SVR had the highest risk of HCC occurrence (13.7%).…”
Section: Prediction Of Clinical Outcomesmentioning
confidence: 86%
“…Therefore, there is a strong need for methods to assess individual patient risk. In a recent prospective multicenter study including 1054 patients with advanced fibrosis (stiffness >10 kPa) or cirrhosis (58% of the total) with a minimum of a six-month follow-up after DAAs, Ampuero et al investigated the predictors of HCC [ 126 ]. HCC was observed in 56 patients (5.3%) after therapy and was independently predicted by Fibrosis-4 (FIB-4) > 3.25 (hazard ratio [HR] 2.26 [1.08–4.73]; p = 0.030), liver stiffness by transient elastography (HR 1.02 [1.00–1.04]; p = 0.045) and baseline cirrhosis by ultrasound (HR 3.15 [1.36–7.27]; p = 0.007).…”
Section: The Impact Of Antiviral Therapy On the Risk Of Hcc In Patients With Chronic Viral Infectionmentioning
confidence: 99%
“…More interestingly, a combination of baseline FIB-4 > 3.25 and HCC screening criteria (cirrhosis or liver stiffness > 10 kPa) had an annual incidence > 1.5 cases per 100 person-years, while the patients lacking these predictors remained at <1 case. Patients who maintained post-treatment FIB-4 > 3.25 and were either cirrhotics or had baseline liver stiffness >10 kPa remained at the highest risk of HCC occurrence (13.7% [21/153] vs. 4.9% [9/184]; logRank 7.396, p = 0.007) [ 126 ].…”
Section: The Impact Of Antiviral Therapy On the Risk Of Hcc In Patients With Chronic Viral Infectionmentioning
confidence: 99%
“…Pretratamiento, el mayor riesgo de CHC fue identificado por la combinación de FIB-4 >3,25 con ET >10 kPa o cirrosis por ecografía. El riesgo de CHC se triplicaba si mantenían estos criterios a los 6 meses tras fin del tratamiento 35 . Es llamativo que no desarrolló CHC ninguno de los pacientes que pretratamiento tenían 10-13,5 KPa, sin cirrosis en ecografía y FIB-4 <3,25; lo que sugiere que en ellos se podría evitar el cribado, por muy bajo riesgo de CHC.…”
Section: Estudio De J Ampuerounclassified
“…Alonso observó el mayor descenso de la RHM y del FIB-4 en el primer año, aunque a los 3 años siguieron descendiendo (probablemente continuó la regresión hepática). Es destacable que el estudio de Ampuero y de Ioannou obtuvieron resultados similares [35][36][37] .…”
Section: ¿Qué Pacientes Tras La Respuesta Viral Sostenida Con Antivir...unclassified